2017
DOI: 10.1159/000477243
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Podocytopathies in Adults: The Next Generation

Abstract: Idiopathic nephrotic syndrome may have two underlying mechanisms: either (1) an alteration of the immune system resulting in the production of a putative circulating factor of glomerular permeability; or (2) mutations in the structural genes of the glomerular filtration barrier in which case patients are typically multidrug resistant and do not recur after transplantation. The latter forms have been recently recognized as “hereditary podocytopathies.” In the past few years, positional cloning approaches that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…More than 50 genes related to FSGS have been described so far, most of them related to function or structure of podocytes. The identification of these genes and the understanding of the role of the mutation type in physiopathology and genotype/phenotype characterization have redefined diagnosis, treatment, and prognosis of nephrotic syndrome 11,12 . The genetic causes of FSGS may present as sporadic or familial disease, with autosomal dominant, autosomal recessive, X-linked, or mitochondrial (matrilineal) inheritance patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 50 genes related to FSGS have been described so far, most of them related to function or structure of podocytes. The identification of these genes and the understanding of the role of the mutation type in physiopathology and genotype/phenotype characterization have redefined diagnosis, treatment, and prognosis of nephrotic syndrome 11,12 . The genetic causes of FSGS may present as sporadic or familial disease, with autosomal dominant, autosomal recessive, X-linked, or mitochondrial (matrilineal) inheritance patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the gene mutations (Table 2) that cause childhood and adulthood disease presentation are discussed below. A more detailed review of gene mutations related to FSGS may be found elsewhere 12 . Footnote: #response in heterozygous mutation has been reported; *partial response has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…is usually manifested in childhood as idiopathic steroid resistant nephrotic syndrome (SRNS). For FSGS two main pathogenic mechanisms are assumed: either (1) an alteration of the immune system resulting in the production of a putative circulating glomerular permeability factor; or (2) mutations in more than 50 structural genes of the glomerular filtration barrier, mainly in the podocytes for which they are named hereditary podocytopathies[17]. Genetic mutations that are responsible for non syndromic FSGS include those that encode SD associated and adaptor proteins such as NPHS1, NPHS1+ NPHS2, NPHS2, CD2AP, TRPC6, PTRO, CRB2, PLCe1), actin-based cytoskeleton complex and signaling including at least ACTN4, MYH9, INF2 , MYO1E, ARHGAP24, ARHGDIA and ANLN or nuclear transcriptional factor (WT1)[9,[17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…For FSGS two main pathogenic mechanisms are assumed: either (1) an alteration of the immune system resulting in the production of a putative circulating glomerular permeability factor; or (2) mutations in more than 50 structural genes of the glomerular filtration barrier, mainly in the podocytes for which they are named hereditary podocytopathies[17]. Genetic mutations that are responsible for non syndromic FSGS include those that encode SD associated and adaptor proteins such as NPHS1, NPHS1+ NPHS2, NPHS2, CD2AP, TRPC6, PTRO, CRB2, PLCe1), actin-based cytoskeleton complex and signaling including at least ACTN4, MYH9, INF2 , MYO1E, ARHGAP24, ARHGDIA and ANLN or nuclear transcriptional factor (WT1)[9,[17][18][19][20][21][22][23][24]. Syndromic FSGS may be a consequence of genetic mutations that are responsible for mutations in GBM proteins such as the mutated COL4 genes in Alport syndrome, WT-1in Denys-Drash (DDS) and Frasier syndrome (FS), LMX1B in nail-patella syndrome, metabolic disorders such as GLA, encoding -galactosidase A in Fabry disease, and mitochondriopathies (mitochondrial tRNA mutations in MELAS syndrome, and COQ2 mutations[9,17,18,25].…”
mentioning
confidence: 99%
See 1 more Smart Citation